JURIDICAL ANALYSIS OF THE ROLE OF CRIMINAL INTENT (MENS REA) IN THE PROOF OF NARCOTICS OFFENSES IN DECISION NUMBER 395/PID.SUS/2025/PN STB - Tulus Halomoan Simanjuntak; Syahrul Bakti Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the results of the study, it shows that the legal regulation of attempted criminal acts or conspiracy in narcotics crimes is regulated in Article 132 of Law Number 35 of 2009 concerning Narcotics. The position of mens rea proof in narcotics crime cases is very important, strategic and fundamental because it directly affects justice and the success of law enforcement. The judge's consideration of the mens rea element in trying narcotics crimes in Decision 395 / Pid.Sus / 2025 / PN Stb has been carried out and is appropriate because it is based on evidence of witness statements, defendant statements, written evidence explaining that the weight of narcotics exceeds 5 grams, and truly contains Methamphetamine and is registered in Class I (one). The defendant's statement stated that the discovery of class I narcotics was for selling them.